Hepatoprotective Effects of Sophoricoside against Fructose‐Induced Liver Injury via Regulating Lipid Metabolism, Oxidation, and Inflammation in Mice. Issue 2 (19th January 2018) - Li, Wenfeng; Lu, Yalong
Abstract : Abstract: The dried fruit of Sophora japonica L. is a traditional Chinese herb tea rich in sophoricoside that is an isoflavone glycoside. The aim of current study was to investigate the hepatic protective effect of sophoricoside in high fructose (HF) diet fed mice. Healthy male mice were fed 30% fructose water and treated 80 and 160 mg/kg·bw sophoricoside continuously for 8 wk. Our data showed that administration of sophoricoside at 80 and 160 mg/kg·bw observably decreased the body weight and liver weight in HF‐fed mice. It was found that the treatment of sophoricoside decreased the hepatic cholesterol and triglyceride levels, and serum low‐density lipoprotein‐cholesterol and apolipoprotein‐B levels, and elevated the serum high‐density lipoprotein‐cholesterol and apolipoprotein‐A1 levels. Moreover, the administration of sophoricoside decreased the HF‐caused elevations of hepatic malonaldehyde, interleukin‐1 and tumor necrosis factor‐α levels, while increased the HF‐induced decreases of hepatic superoxide dismutase and glutathione peroxidase activities. Meanwhile, serum aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase activities were reduced by treatment of sophoricoside in HF‐fed mice. Histopathology of hematoxylin and eosin (H&E) and oil red O staining of liver tissues also confirmed the beneficial effects of sophoricoside against liver injury induced by HF‐diet in mice. These findings indicated that sophoricoside may be a novel natural isoflavone for alleviating HF‐induced liver injury. Practical Application: Fruit of Sophora japonica L. is a traditional herb tea and it recently becomes popular in China. Sophoricoside is an isoflavone glycoside (Genistein‐4'‐ O ‐β‐d ‐glucopyranoside) isolated from S. japonical L, and it possessed differential effects on the body health. The ingestion of sophoricoside or sophora fruit tea may be a novel strategy to prevent non‐alcoholic fatty liver disease.